No Change in Bicarbonate Transport but Tight-Junction Formation Is Delayed by Fluoride in a Novel Ameloblast Model - Rácz, Róbert; Földes, Anna; Bori, Erzsébet; Zsembery, Ákos; Harada, Hidemitsu; Steward, Martin C.; DenBesten, Pamela; Bronckers, Antonius L. J. J.; Gerber, Gábor; Varga, Gábor (Frontiers in Physiology, 2017)
We have recently developed a novel in vitro model using HAT-7 rat ameloblast cells to functionally study epithelial ion transport during amelogenesis. Our present aims were to identify key transporters of bicarbonate in HAT-7 cells and also to examine the effects of fluoride exposure on vectorial bicarbonate transport, cell viability and the development of transepithelial resistance. To obtain monolayers, the HAT-7 cells were cultured on Transwell permeable filters. We monitored transepithelial resistance (TER) as an indicator of tight junction formation and polarization. We evaluated intracellular pH changes by microfluorometry using the fluorescent indicator BCECF. Activities of ion transporters were tested by withdrawal of various ions from the bathing medium, by using transporter specific inhibitors, and by activation of transporters with forskolin and ATP. Cell survival was estimated by alamarBlue assay. Changes in gene expression were monitored by qPCR. We identified the activity of several ion transporters, NBCe1, NHE1, NKCC1 and AE2, which are involved in intracellular pH regulation and vectorial bicarbonate and chloride transport. Bicarbonate secretion by HAT-7 cells was not affected by acute fluoride exposure over a wide range of concentrations. However, tight-junction formation was inhibited by 1 mM fluoride, a concentration which did not substantially reduce cell viability, suggesting an effect of fluoride on paracellular permeability and tight-junction formation. Cell viability was only reduced by prolonged exposure to fluoride concentrations greater than 1 mM. In conclusion, cultured HAT-7 cells are functionally polarized and are able to transport bicarbonate ions from the basolateral to the apical fluid spaces. Exposure to 1 mM fluoride has little effect on bicarbonate secretion or cell viability but delays tight-junction formation, suggesting a novel mechanism that may contribute to dental fluorosis.